2005
DOI: 10.1002/gps.1263
|View full text |Cite
|
Sign up to set email alerts
|

Components of behavioral pathology in dementia

Abstract: The finding of three factors of behavioral pathology in demented patients reflects the possibility that different etiological mechanisms could explain the expression of the symptoms and signs of psychosis in demented patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 66 publications
4
22
0
6
Order By: Relevance
“…The inclusion of night-time behaviour disturbances in the psychosis factor is in accordance with findings of Schreinzer et al [24] , who found a factor representing diurnal rhythm disturbances and hallucinations. They concluded that their factor did not fulfil the criteria for delirium but nevertheless implied that it was of clinical importance because these symptoms require specific treatment strategies.…”
Section: Discussionsupporting
confidence: 76%
“…The inclusion of night-time behaviour disturbances in the psychosis factor is in accordance with findings of Schreinzer et al [24] , who found a factor representing diurnal rhythm disturbances and hallucinations. They concluded that their factor did not fulfil the criteria for delirium but nevertheless implied that it was of clinical importance because these symptoms require specific treatment strategies.…”
Section: Discussionsupporting
confidence: 76%
“…Likewise, night-time behaviour disturbances had high loadings on the psychosis and apathy subsyndromes, but it was decided to include them in the factor psychosis. The inclusion of night-time behaviour disturbances in the psychosis factor is in accordance with the findings of Schreinzer et al [12] , who found a factor representing diurnal rhythm disturbances and hallucinations. They concluded that their factor did not fulfil the criteria for delirium but nevertheless implied it was of clinical importance because these symptoms require specific treatment strategies.…”
Section: Discussionsupporting
confidence: 77%
“…The results show that apathy is a perceived challenge and associated with increased workload (Cummings, 1997;Ballard et al, 2001;Starkstein et al, 2005). Agitation, disinhibition, irritability and aberrant motor behaviours are inter-related neuropsychiatric symptoms (Lange et al, 2004, Schreinzer et al, 2005. They are more common in later stage dementia patients as revealed in this sample.…”
Section: Discussionmentioning
confidence: 44%